Mechanistic Study of Schisandra chinensis Fruit Mixture Based on Network Pharmacology, Molecular Docking and Experimental Validation to Improve the Inflammatory Response of DKD Through AGEs/RAGE Signaling Pathway - Li H; Dong A; Li N; Ma Y; Zhang S; Deng Y; Chen S; Zhang M (Drug Design, Development and Therapy, 2023)
Hongdian Li,1,* Ao Dong,1,* Na Li,1 Yu Ma,1 Sai Zhang,1 Yuanyuan Deng,1 Shu Chen,1 Mianzhi Zhang1,2 1Department of Nephrology, Dongfang Hospital of Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Department of Nephrology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mianzhi Zhang, Email zhangmianzhi@vip.sina.comBackground: Diabetic kidney disease (DKD) is a major cause of end-stage renal disease (ESRD), and inflammation is the main causative mechanism. Schisandra chinensis fruit Mixture (SM) is an herbal formulation that has been used for a long time to treat DKD. However, its pharmacological and molecular mechanisms have not been clearly elucidated. The aim of this study was to investigate the potential mechanisms of SM for the treatment of DKD through network pharmacology, molecular docking and experimental validation.Methods: The chemical components in SM were comprehensively identified and collected using liquid chromatography-tandem mass spectrometry (LC-MS) and database mining. The mechanisms were investigated using a network pharmacology, including obtaining SM-DKD intersection targets, completing protein–protein interactions (PPI) by Cytoscape to obtain key potential targets, and then revealing potential mechanisms of SM for DKD by GO and KEGG pathway enrichment analysis. The important pathways and phenotypes screened by the network analysis were validated experimentally in vivo. Finally, the core active ingredients were screened by molecular docking.Results: A total of 53 active ingredients of SM were retrieved by database and LC-MS, and 143 common targets of DKD and SM were identified; KEGG and PPI showed that SM most likely exerted anti-DKD effects by regulating the expression of AGEs/RAGE signaling pathway-related inflammatory factors. In addition, our experimental validation results showed that SM improved renal function and pathological changes in DKD rats, down-regulated AGEs/RAGE signaling pathway, and further down-regulated the expression of TNF-α, IL-1β, IL-6, and up-regulated IL-10. Molecular docking confirmed the tight binding properties between (+)-aristolone, a core component of SM, and key targets.Conclusion: This study reveals that SM improves the inflammatory response of DKD through AGEs/RAGE signaling pathway, thus providing a novel idea for the clinical treatment of DKD.Keywords: Schisandra chinensis fruit mixture, diabetic kidney disease, traditional Chinese medicine, network pharmacology, molecular docking